Recent advances in CRISPR-Cas9-based genome insertion technologies - Xinwen Chen; Jingjing Du; Shaowei Yun; Chaoyou Xue; Yao Yao; Shuquan Rao (Elsevier, 2024)
Programmable genome insertion (or knock-in) is vital for both fundamental and translational research. The continuously expanding number of CRISPR-based genome insertion strategies demonstrates the ongoing development in this field. Common methods for site-specific genome insertion rely on cellular double-strand breaks repair pathways, such as homology-directed repair, non-homologous end-joining, and microhomology-mediated end joining. Recent advancements have further expanded the toolbox of programmable genome insertion techniques, including prime editing, integrase coupled with programmable nuclease, and CRISPR-associated transposon. These tools possess their own capabilities and limitations, promoting tremendous efforts to enhance editing efficiency, broaden targeting scope and improve editing specificity. In this review, we first summarize recent advances in programmable genome insertion techniques. We then elaborate on the cons and pros of each technique to assist researchers in making informed choices when using these tools. Finally, we identify opportunities for future improvements and applications in basic research and therapeutics.